2004
DOI: 10.1159/000076471
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Trends of Clarithromycin-Resistant <i>Helicobacter pylori</i> Isolates in Japan over a Decade

Abstract: Clarithromycin has been administered to patients in Japan since 1991. Clarithromycin-resistant Helicobacter pylori strains have been on the rise in Japan. We obtained H. pylori isolates between 1989 and 2000 and examined mutations of the 23S rRNA gene, which are closely associated with clarithromycin resistance. Isolates were obtained from 356 patients with H. pylori infection treated at the Hiroshima University. Sixty-one of the patients received clarithromycin-based H. pylori eradication therapy. Mutations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 18 publications
1
17
0
1
Order By: Relevance
“…However, it was unfortunately only approved as first eradication regimen in Japan. Our eradication rate was similar to the previous Japanese reports ,, and relatively higher compared to the results of Korean studies (0~12.5%) investigating the small number of subjects with 23S rRNA A2143G mutant ,. As a rapid increase in CAM resistance led to a fall in cure rates to 80% or less, CAM must be avoided as H. pylori eradication regimen unless the CAM susceptibility can be confirmed.…”
Section: Discussionsupporting
confidence: 88%
“…However, it was unfortunately only approved as first eradication regimen in Japan. Our eradication rate was similar to the previous Japanese reports ,, and relatively higher compared to the results of Korean studies (0~12.5%) investigating the small number of subjects with 23S rRNA A2143G mutant ,. As a rapid increase in CAM resistance led to a fall in cure rates to 80% or less, CAM must be avoided as H. pylori eradication regimen unless the CAM susceptibility can be confirmed.…”
Section: Discussionsupporting
confidence: 88%
“…It has also been suggested that a combination of MTZ and CL promotes the selection of secondary CL resistance more readily than regimens containing CL and AMX [19]. Helicobacter pylori resistance to CL has been reported to be increasing in many countries [20,21], which is associated with an extensive therapeutic use of macrolides. Our study showed high rates both of overall and primary H. pylori resistance to CL, with great variations between the centres (ranging from 0% to 33%).…”
Section: Discussionmentioning
confidence: 99%
“…They observed an increase in macrolide resistance from 0 to 20.4% over the 12 years follow‐up period. The eradication rate was 72% for susceptible strains and 36.4% for resistant strains [8].…”
Section: Culturementioning
confidence: 99%